Perancangan Pencahayaan Di Gedung Baru Sekolah Tinggi Teknologi Pekanbaru (STTP) - Mulya Feri; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Lightening is one of important factors in designing a room. Lightening intensity does not meet the standards can affect eye health and work activities. In this study measurement of Lightening intensity strongly is carried out in the New Building of the Sekolah Tinggi Teknologi Pekanbaru (STTP). From the measurement that have been made is less than the standard, which expected based on SNI 6197-2011. Therefore, evaluation and recalculation the number of lamp is carried out by using the zonal cavity method and then, it is simulated by using software dialux evo 8.1. From the results of calculation using the zonal cavity method, the Lightening strong expected for the rooms can be derived and simulates using software dialux display a room in three-dimensional form displays the strong results of the Lightening intensity in the room directly. In using dialux software, there are three types of lamp used, namely attach lamp, in hanging lamp and down light lamp.Keywords: SNI 6197-2011, Lamp, Zonal Cavity Methods, software dialux evo 8.1, variation of lamp.